The impact of human capital management on operational performance at the Gambia National Water and Electricity Company (NAWEC) - Nicol-Keita Grace, Rachel (2015)
A Thesis submitted to the Department of Managerial Science, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF BUSINESS ADMINISTRATION (HRM OPTION).